Changes in the health literacy of residents aged 15–69 years in central China: A three-round cross-sectional study - Mei, Xin; Chen, Gong; Zuo, Yuting; Wu, Qian; Li, Junlin; Li, Yilin (Frontiers in Public Health, 2023)
Health literacy is an effective strategy to promote more cost-effective use of health care services and a crucial tool for preventing the spread of infectious diseases. The main objective of this study was to analyze changes in health literacy from 2019 to 2021. Data were from the latest three-round cross-sectional studies with the same study design. Although the prevalence of adequate health literacy rose significantly over time, increasing from 26.9% (95% CI 20.1-33.7) in 2019 to 34.1% (32.9-35.3) in 2021, it was still at a relatively low level. The most significant decrease was observed for health skills among the three aspects and health information literacy among the six dimensions. Working as medical staff was a protective factor for adequate health literacy, health skills literacy, and health information literacy. Risk factors for adequate health literacy and health information literacy were older age and lower education level. Furthermore, adequate health information literacy was positively related to annual family income. More practical and effective policies targeting health literacy for critical aspects and groups in Central China, are urgently needed, especially during the epidemic.